Kajian Hukum Pemberian Perintah Tertulis di Sektor Jasa Keuangan oleh Otoritas Jasa Keuangan dalam Rangka Perlindungan Konsumen Sektor Jasa Keuangan - Septrina, Theresia (LPPM Universitas Ekasakti Padang, 2024)
In essence, law enforcement is the process of making efforts to enforce or function real legal norms as guidelines for behavior in traffic or legal relations in social and state life. Thus, in short, law enforcement is an effort made to make the law, both in the narrow formal sense and in the broad material sense, a guideline for behavior in every legal act, both by the legal subjects concerned and by law enforcement officials who are officially given duties and authorities by law to ensure the functioning of legal norms that apply in social and state life. Law enforcement efforts for violations of written orders are carried out by imposing sanctions as regulated in the provisions regarding written orders, namely criminal sanctions as regulated in the OJK Law. In its development, sanctions for violations of written orders are not only in the form of criminal sanctions but also administrative sanctions, this can be seen from the regulations in POJK Number 35/POJK.05/2016 concerning Procedures for Determining Written Orders in the Insurance Sector, POJK Number 18/POJK.3/ 2020 concerning Written Orders for Handling Bank Problems, and POJK 40/POJK.05/2020 concerning Written Orders for Handling Nonbank LJK Problems, apart from criminal sanctions as regulated in the OJK Law there are also administrative sanctions for violations of written orders, namely in the form of written warnings, restrictions business activities, and revocation of business permits, written warnings and prohibitions as the main party. This can be interpreted as meaning that criminal sanctions in efforts to enforce the law of written orders in the financial services sector are imposed as ultimum remidium.